2020
DOI: 10.1063/5.0013504
|View full text |Cite
|
Sign up to set email alerts
|

Toward quantum efficiency enhancement of kesterite nanostructured absorber: A prospective of carrier quantization effect

Abstract: In this work, the carrier confinement mechanism through nanostructures is studied in a copper-zinc-tin-sulfide/Cu2ZnSnSe4-type kesterite material, resulting in a remarkable performance enhancement of solar cells. The effect of the quantized energy band, recombination rate, and escape mechanism on the spectral response of solar cells is explored in detail. The mathematical model for carrier dynamics and performance measuring parameters are analyzed and optimized. Moreover, the number of quantum wells is incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Incorporation of lesser bandgap compared to bulk material provides the advantages to absorb more number of photons from the solar spectrum. [ 18,30,31 ] These interesting phenomena help researcher to achieve more than 42% efficiency theoretically. [ 32 ] In this work, two‐dimensionally confined quantum wells (QWs) are proposed as a nanostructure with bulk material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of lesser bandgap compared to bulk material provides the advantages to absorb more number of photons from the solar spectrum. [ 18,30,31 ] These interesting phenomena help researcher to achieve more than 42% efficiency theoretically. [ 32 ] In this work, two‐dimensionally confined quantum wells (QWs) are proposed as a nanostructure with bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] In addition to this, incorporation of nanostructure with carrier confinement increases the overall performance of solar cell as compared to bulk solar cell. [18][19][20][21] On the other hand, the performance of CFTS and CFTSe is less explored. The material possesses the capability to reduce defects and traps as compared to CZTS.…”
mentioning
confidence: 99%
“…The detailed description of models and equations used in this study can be found in the supplementary material. [ 16 ] Silvaco ATLAS technology computer‐aided design (TCAD) tool is used to analyze the functioning and performance of these photovoltaic devices. [ 17 ] The simulation of these devices is carried out under an illumination spectrum power of 1 sun with air mass 1.5 global spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…All the mathematical expressions for four performance measuring parameters with only traps and only defects can be found in the previous studies. [ 8,16 ] The reverse saturation current density is calculated, considering non‐radiative recombination, the presence of defects states, and trap states. Shockley–Read–Hall (SRH) recombination mechanism is applied to incorporate the effect of trap states near the middle of the forbidden gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation